"How Old Do You Feel?" The Difficulties and Ethics of Operationalizing Subjective Age. (16th June 2017) - Gendron, Tracey L; Inker, Jennifer; Welleford, Ayn
Abstract: This article provides an integrative presentation regarding ageism within the professional culture of gerontological research by examining the operationalization of subjective age, a construct most commonly assessed by asking an individual to report how "old" they feel. According to the life span perspective [Baltes, P. B. (1987). Theoretical propositions of lifespan developmental psychology: On the dynamics between growth and decline. Developmental Psychology, 23, 611–626] and the life course perspective [Elder Jr, G. H. (1975). Age differentiation and the life course. Annual Review of Sociology, 1(1), 165–190.], growing older represents a complex, multidirectional process that encompasses maintenance, growth and decline as well as cultural factors that influence development. Viewing the construct of subjective age from these perspectives casts doubt on the validity of its operationalization. This article argues that operationalizing subjective age in this manner contributes to the dominant societal view of aging as decline by perpetuating the use of the term "old" as an undesirable state. As well, we purport that as gerontological researchers and scholars our professional code of ethics requires us to examine the unintentional communication and perpetuation of ageism by focusing attention on our own use of language.